Analysis of the Procedure for Service of Certificates of Disabled in the Village Office Lasitae, Tanete District, Rilau Barru District - Aidah, Aidah (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This research aims to find out: Analysis of the Procedure for Service of Indigent Certificates at the Lasitae Village Office, Tanete Rilau District, Barru Regency. This type of research is quantitative, which is intended to provide a clear picture of the problems being studied, interpreting and explaining the data systematically. Data sources were obtained through questionnaires and observations. The results of this research indicate that the analysis of the procedures for providing disability certificates at the Lasitae Village Office, Tanete Rilau District, Barru Regency is in accordance with good service procedures by looking at the results of the hypothesis test output, a sig value is obtained. (2-tailed) ? ? (0.05) i.e. 0.000 ? 0.05. Employee resources still need to be adjusted to skills and experience.